Determinants of Islamic Religious Education Teachers Performance in Relation to Motivation, Professional Competence, and Gratitude - Anwar, Khairil; Sabrina, Rifdah; Ahmad, Azizan (Fitrah: Journal of Islamic Education, 2025)
Teacher performance in Indonesia is often influenced by internal factors such as work motivation, professional competence, and gratitude, which play crucial roles in learning effectiveness. However, the balance between psychological, professional, and spiritual aspects in improving teacher performance has received limited attention. This study aims to analyze the differences, relationships, and effects of work motivation, professional competence, and gratitude on teacher performance. The research employed a quantitative approach with both descriptive and inferential analyses, including t-tests, Pearson correlations, and multiple linear regression. The respondents consisted of 70 teachers from various educational levels in Indonesia. The findings indicate that all four variables fall into the high category. There is no significant difference based on gender, but there are significant differences based on education level, rank, and salary. Regression analysis shows a simultaneous influence of 48%, with gratitude emerging as the most dominant factor (β = 0.401). These findings highlight the importance of maintaining a balance between spiritual and professional dimensions in enhancing teacher performance. The implication is that educational institutions should strengthen teachers’ competence, motivation, and spirituality.